1966
DOI: 10.1084/jem.124.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Hastens

Abstract: Groups of rabbits were injected with either bovine serum albumin, sheep red cell stroma, or keyhole limpet hemocyanin to which 2,4-dinitrophenyl and/or p-azophenyl arsonate groups had been coupled. Groups of animals received either doubly coupled antigen or an equivalent mixture of singly coupled antigens. Materials were injected intravenously as a solution or subcutaneously and intramuscularly in complete Freund's adjuvant. The presence of dinitrophenyl groups on the immunizing antigen could su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This is suggested by the observation recently reported by Arnkraut et al (18) that, in their systems, competition occurred only when both haptens were on the same carrier molecule. Thus, the results obtained in such comparisons may be dependent upon a variety of variables, e.g., nature of the two haptens, nature of the carrier molecules, degree of substitution, dose of antigens used in immunization, etc.…”
Section: Discussionmentioning
confidence: 54%
“…This is suggested by the observation recently reported by Arnkraut et al (18) that, in their systems, competition occurred only when both haptens were on the same carrier molecule. Thus, the results obtained in such comparisons may be dependent upon a variety of variables, e.g., nature of the two haptens, nature of the carrier molecules, degree of substitution, dose of antigens used in immunization, etc.…”
Section: Discussionmentioning
confidence: 54%
“…R-bovine serum albumin (R-BSA) was prepared as previously described [14], a method which yields a coupling ratio of R24-BSA. Rhesus monkeys were immu nized with 1 mg R-Tyr in complete Freund's adjuvant distributed s. c. in small doses in the lateral areas of the body.…”
Section: Methodsmentioning
confidence: 99%
“…Competition phenomena between synthetic antigens (5,6) as well as between hapten conjugates (3,(7)(8)(9)(10)(11)(12) have been reported. Adler (3) showed that the introduction of p-azobenzenearsonate residues into ferritin impaired the formation of anti-ferritin antibodies in mice.…”
Section: (From the Section Of Chemical Immunology The Weizmann Instimentioning
confidence: 99%
“…Adler (3) showed that the introduction of p-azobenzenearsonate residues into ferritin impaired the formation of anti-ferritin antibodies in mice. Amkraut et al (10) found, in rabbits, that immunization with doubly substituted carrier (bovine serum albumin, sheep red cell stroma, or keyhole limpet hemocyanin) enabled the dinitrophenyl groups to suppress the antibody response to p-azobenzenearsonate. Recently Siskind et al (12), who also used these haptens, reported decreased antibody formation in rabbits against both determinants.…”
Section: (From the Section Of Chemical Immunology The Weizmann Instimentioning
confidence: 99%